2023
DOI: 10.1186/s13071-022-05562-7
|View full text |Cite
|
Sign up to set email alerts
|

First record of Trypanosoma evansi DNA in Dichelacera alcicornis and Dichelacera januarii (Diptera: Tabanidae) flies in South America

Abstract: Background Trypanosoma evansi infects a large number of wild and domestic animals and causes a spoliative disease known as surra. It is mechanically transmitted, mainly by biting flies of the genera Tabanus and Stomoxys. The detection of T. evansi DNA in the feeding apparatus of Dichelacera alcicornis and Dichelacera januarii from South America is reported, to the best of our knowledge, for the first time. Methods Tabanids were collected weekly fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Tabanidae (horse flies) comprise approximately 4,525 species ( Pape & Thompson, 2023 ), of which 27% are found in the Neotropical region ( Henriques et al, 2012 ). Several species are mechanical vectors of pathogens to humans and animals ( Baldacchino et al, 2014 ; Taioe et al, 2017 ; Bilheiro et al, 2019 ; Rodrigues et al, 2021 ; 2022 ; Ramos et al, 2023 ). Tabanid studies have focused on females because, since they need a blood meal before ovipositing, they are the vectors of pathogens ( Barros, 2001 ; Rafael & Charlwood, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tabanidae (horse flies) comprise approximately 4,525 species ( Pape & Thompson, 2023 ), of which 27% are found in the Neotropical region ( Henriques et al, 2012 ). Several species are mechanical vectors of pathogens to humans and animals ( Baldacchino et al, 2014 ; Taioe et al, 2017 ; Bilheiro et al, 2019 ; Rodrigues et al, 2021 ; 2022 ; Ramos et al, 2023 ). Tabanid studies have focused on females because, since they need a blood meal before ovipositing, they are the vectors of pathogens ( Barros, 2001 ; Rafael & Charlwood, 1980 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ecological studies in the same area showed that the activity peak of adult insects occurred in the hottest periods of the year (late spring and summer) and suggested that Tabanus triangulum Wiedemann, 1828 was a strong candidate for the mechanical transmission of pathogens in the region, due to its prevalence there ( Krüger & Krolow, 2015 ). Recently, Trypanosoma evansi DNA was found in the mouthparts of Dichelacera alcicornis (Wiedemann, 1828) and D. januarii (Wiedemann, 1819) ( Ramos et al, 2023 ) in the state of Santa Catarina (first record for South America). In the Pantanal biome, Barros (2001) noticed that the rainy season offers the highest risk of mechanical transmission of pathogenic agents by tabanids.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological studies in the same area corroborate that the activity peak of adult insects occurs in the hottest periods of the year (late spring and summer) and suggest that Tabanus triangulum Wiedemann, 1828 is a strong candidate for the mechanical transmission of pathogens in the region, due its prevalence there (Krüger and . Recently, Trypanosoma evansi DNA was found in the mouthparts of the tabanids Dichelacera alcicornis (Wiedemann, 1828) and D. januarii (Wiedemann, 1819) (Ramos et al 2023) in the state of Santa Catarina ( rst record for South America). In the Pantanal biome, Barros (2001) noticed that the rainy season offers the highest risk of mechanical transmission of pathogenic agents by tabanids.…”
Section: Introductionmentioning
confidence: 99%